COMPARISON OF THE EFFECTIVENESS OF RHAMNOLIPID AND SOPHOROLIPID BIOSURFACTANTS IN BEREA SANDSTONE FOR ADVANCED APPLICATIONS OF ENHANCED OIL RECOVERY - Ahyuriza, Savira
Biotechnology is the application of technology to biological systems to produce products or processes that are more efficient and environmentally friendly. In the context of enhanced oil recovery technology development, biotechnology can be used to develop new more environmentally friendly and sustainable methods by developing microorganisms that can be used to increase recovery factor efficiency, such as biosurfactants. Rhamnolipids and sophorolipids are non-toxic, biodegradable biosurfactants that are environmentally friendly substances. This study compares the results of laboratory studies on fluid-to-fluid interactions, including testing of interfacial tension and fluid-to-rock interactions, namely testing of contact angles and core flooding at various concentrations and salinities. The mechanism of these two biosurfactants is based on limiting the interfacial tension between the fluids and changing the wettability of the rock to a more water-wet state. In the interfacial test, the interfacial tension of rhamnolipids reaches mN/m, whereas that of sophorolipids only reaches mN/m. Then, the sandstone wettability test showed that the two biosurfactants were classified as water-wet (<75?). In a salinity range of 8000–32000 ppm, rhamnolipids perform better at higher salinities to reduce interfacial tension, and salinity has a subtle effect on the contact angle. Lastly, in the core flood test, the sophorolipids have a high recovery factor value and are more effective than the rhamnolipids, but the two biosurfactants can increase the recovery factor. This happens because of its chemical structure, which has two parts: the hydrophobic part (which likes oil or non-polar substances) and the hydrophilic part (which likes air or polar substances). These two biosurfactants increase oil recovery in sandstone, especially in enhanced oil recovery applications, so that they can contribute to environmentally friendly biotechnology.